Maximizing Cognitive Learning: Active Participation with Audiovisual Media: Optimisasi Hasil Belajar Kognitif Siswa melalui Partisipasi Aktif dan Media Audiovisual: Penelitian Empiris - Intan Nur Azian; Feri Tirtoni (Universitas Muhammadiyah Sidoarjo, 2023)
This study aimed to investigate the impact and magnitude of audiovisual media on students' cognitive learning outcomes through active engagement in the learning process. The research was conducted in a fifth-grade class comprising 30 students at SDN 1 Paciran. The saturated sampling technique was employed, and data were collected through a series of descriptive essay questions, consisting of 10 items. The participants' cognitive learning outcomes were assessed using pretest and posttest measures. Descriptive statistics and t-test analysis were employed for data analysis. The findings revealed a significant increase in students' average scores for cognitive learning outcomes, with a notable improvement of 18.07 points from the pretest score of 59.50 to the posttest score of 77.57. The results of the t-test indicated a positive influence of audiovisual media on students' cognitive learning outcomes. This study provides valuable insights into the efficacy of audiovisual media in fostering meaningful learning and enhancing students' cognitive abilities, highlighting the importance of incorporating such media into educational practices. Highlights: Active engagement: The study emphasizes the significance of active participation in the learning process to enhance cognitive learning outcomes. Impact of audiovisual media: The research explores the effect and magnitude of using audiovisual media on students' cognitive learning outcomes. Empirical investigation: The study employs a rigorous empirical approach to gather and analyze data, providing reliable insights into the relationship between audiovisual media and cognitive learning outcomes. Keywords: cognitive learning outcomes, active participation, audiovisual media, empirical investigation, students.